Commentary Elite youth sports — The year that was 2017 - Williams, C. A. (Pediatric Exercise Science, 2018)
In 2017, considerable attention has been paid by researchers on early sports specialization for youth athletes. Issues related to injury, burnout, and talent development to name a few have been debated, particularly when contrasted against other opposing youth development approaches, such as a multisport approach. The increasing professionalization of young athletes, a particular concern of this author, is coupled with the ensuing physical and mental pressures on these youngsters, as highlighted by the 2 highlighted publications in this commentary. Moreover, the financial costs to parents to support talented youngsters lead me to conclude that we must not treat them as "mini-adult athletes." Trying to predict too far into the sporting future of a 9- or 10-year athlete can lead us to forgetting that they are just a 9 year, who typically wants to play, have fun, and be with their friends. Embarking on concentrated training programs, endless travel for tournaments, and an overemphasis on winning can be detrimental to participation rates as shown by recent data in the United States. Therefore, the challenge for researchers in elite youth sports is to ensure that practices we pursue with our young charges promote their health and well-being and that sports is for the benefit of the athlete and not the other way around.